Konsep Pendidikan Menurut Al-Ghazali: Studi terhadap Kitab Ayyuhal Walad - Mukaromah, Lailatul; Aly, Hery Noer; Suradi, Ahmad (AS-SABIQUN, 2023)
This study aims to analyze education according to Al-Ghazali in his book Ayyuhal Walad. The research method used in this research is library research using a qualitative research approach. The approach used in this study is a historical approach and a philosophical inquiry approach. The results of this research analysis show that the concept of education contained in the Ayyuhal Walad book is seen from the aspect of the educational objectives offered by Imam Al-Ghazali with the law of year no. 20 of 2003 that the purpose of education is still relevant, namely to form children who draw closer to God. The material contained in the Ayyuhal Walad book is the same as the material taught to students, namely the formation of morals is in the lesson of aqidah morals. Not all of the methods offered by Imam Al-Ghazali are relevant to today's level of modern education, collaboration between Imam Al-Ghazali's methods and existing methods is necessary.